2017
DOI: 10.3382/ps/pew389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term Bacillus subtilis CGMCC 1.921 supplementation on performance, egg quality, and fecal and cecal microbiota of laying hens

Abstract: This study evaluated the effects of long-term Bacillus subtilis CGMCC 1.921 supplementation on the performance, egg quality, and fecal/cecal microbiota of laying hens. A total of 360 28-week-old Hy-Line Brown laying hens were randomly allocated into 5 treatments with 6 replicates of 12 birds each for 24 weeks. The experimental treatments included a basal diet without additions (Con) and the basal diet supplemented with 1.0 × 105 (B1), 1.0 × 106 (B2), 1.0 × 107 (B3), and 1.0 × 108 (B4) cfu/g B. subtilis CGMCC 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 49 publications
10
23
0
2
Order By: Relevance
“…However, Zhang, Zhou, Ao, and Kim () reported that no significant variance was found in yolk colour compared with the control group. Similar results were reported by Lei et al () and Guo et al (), who observed the effect of probiotic supplementation on yolk colour was unclear. The difference results among the various studies might be due to the different probiotic species, experimental period and environmental conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, Zhang, Zhou, Ao, and Kim () reported that no significant variance was found in yolk colour compared with the control group. Similar results were reported by Lei et al () and Guo et al (), who observed the effect of probiotic supplementation on yolk colour was unclear. The difference results among the various studies might be due to the different probiotic species, experimental period and environmental conditions.…”
Section: Discussionsupporting
confidence: 89%
“…However, other researchers found that dietary BS had minimal or no effects on the production performance of laying hens. Guo, Dong, Liu, and Tong () found that dietary supplementation with BS did not significantly influence on the egg production, egg weight and feed intake of 28‐week‐old Hy‐Line laying hens. Forte et al () reported that the effects of supplementation with 0.1% Lactobacillus acidophilus and 0.05% BS on the performance of 16‐week‐old Hy‐Line laying hens and found no differences among the different groups.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that adding Bacillus sp. to the laying hen's feed can signi cantly increase egg production rate, average egg weight, reduce feed conversion ratio, and improve egg quality and immunity [36][37][38][39]. Because eggs are the main products in the laying hen farm, and the egg production rate determines the breeding e ciency.…”
Section: Discussionmentioning
confidence: 99%
“…En estudios recientes han mostrado que utilizando el B. subtilis como probiótico en gallinas ponedoras (Hy-Line Brown) de 28 semanas de edad, puede favorecer la ganancia productiva mejorando de manera efectiva su rendimiento y la calidad a través de la reducción de E. coli fecal y la modulación de la microbiota cecal, mediante el uso de B. subtilis como probiótico; encontrando que la alimentación en relación con la producción de huevo disminuye de manera importante, mejorando además la resistencia de la cáscara del huevo (Guo, Dong, Liu, & Tong, 2016). Por otra parte, Forte et al, (2016) encontraron que mediante el uso de Lactobacillus acidophilus y B. subtilis como probióticos, disminuyeron la presencia de E. coli, estafilococos y clostridios; al tiempo que se incrementa la presencia de bacterias beneficiosas, tales como Lactobacillus spp.…”
Section: Bacillus Subtilis En La Reducción De Bacterias Nocivasunclassified